2018
DOI: 10.48550/arxiv.1811.05697
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Universality of Energy Equipartition in One-dimensional Lattices

Weicheng Fu,
Yong Zhang,
Hong Zhao

Abstract: We show that a general one-dimensional (1D) lattice with nonlinear inter-particle interactions can always be thermalized for arbitrarily small nonlinearity in the thermodynamic limit, thus proving equipartition hypothesis in statistical physics for an important class of systems. Particularly, we find that in the lattices of interaction potential V (x) = x 2 /2+λx n /n with n ≥ 4, there is a universal scaling law for the thermalization time T eq , i.e., T eq ∝ λ −2 −(n−2) , where is the energy density. Numerica… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
1

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 44 publications
(73 reference statements)
3
8
1
Order By: Relevance
“…However, it was also found that for a lattice with asymmetric potential interaction, though T eq still depends on γ in a power law, the exponent deviates from −2. In addition, the numerical result T eq ∼ γ −4.6 for the asymmetric FPU-α model [46] deviates from the conjectured T eq ∼ γ −4 [36] seriously as well.…”
Section: Introductioncontrasting
confidence: 57%
See 4 more Smart Citations
“…However, it was also found that for a lattice with asymmetric potential interaction, though T eq still depends on γ in a power law, the exponent deviates from −2. In addition, the numerical result T eq ∼ γ −4.6 for the asymmetric FPU-α model [46] deviates from the conjectured T eq ∼ γ −4 [36] seriously as well.…”
Section: Introductioncontrasting
confidence: 57%
“…It was further conjectured (but not verified) that the nontrivial four-wave resonant interactions would dominate the thermalization process in the thermodynamic limit, leading to T eq ∼ γ −4 and T eq ∼ γ −2 for the FPU-α [36] and FPU-β [37] model, respectively. These conjectures were partially verified in a very recent effort [46] where it was found that in the thermodynamic limit, a universal law, T eq ∼ γ −2 , applies generally to a class of one-dimensional (1D) lattices with interaction potential V (x) = x 2 /2 + λx n /n, where n ≥ 4 is an integer and γ = λε (n−2)/2 is the nonlinearity strength. It also applies to another class of 1D lattices with symmetric interaction potential V (x) = x 2 /2 + λ|x| d /d, where d = m 1 /m 2 > 2 with m 1 and m 2 being two coprime integers and the nonlinearity strength γ = λε (d−2)/2 .…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations